2008
DOI: 10.1016/j.gene.2007.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the cutinase gene family: Evidence for lateral gene transfer of a candidate Phytophthora virulence factor

Abstract: Lateral gene transfer (LGT) can facilitate the acquisition of new functions in recipient lineages, which may enable them to colonize new environments. Several recent publications have shown that gene transfer between prokaryotes and eukaryotes occurs with appreciable frequency. Here we present a study of interdomain gene transfer of cutinases -well documented virulence factors in fungi -between eukaryotic plant pathogens Phytophthora species and prokaryotic bacterial lineages. Two putative cutinase genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 48 publications
1
52
1
1
Order By: Relevance
“…Several studies of phagotrophic eukaryotes appear to be consistent with the principle of the "you are what you eat hypothesis" because several phagotrophic single-celled protozoa possess genes of recent prokaryotic ancestry Archibald et al, 2003;Eichinger et al, 2005;Loftus et al, 2005). There is, however, also some evidence for HGT involving nonphagotrophic fungi and oomycetes (Garcia-Vallve et al, 2000;Friesen et al, 2006;Richards et al, 2006a;Belbahri et al, 2008).…”
Section: Introductionmentioning
confidence: 81%
“…Several studies of phagotrophic eukaryotes appear to be consistent with the principle of the "you are what you eat hypothesis" because several phagotrophic single-celled protozoa possess genes of recent prokaryotic ancestry Archibald et al, 2003;Eichinger et al, 2005;Loftus et al, 2005). There is, however, also some evidence for HGT involving nonphagotrophic fungi and oomycetes (Garcia-Vallve et al, 2000;Friesen et al, 2006;Richards et al, 2006a;Belbahri et al, 2008).…”
Section: Introductionmentioning
confidence: 81%
“…A review of published reports of HGT can didates demonstrates that genes encoding secreted enzymes (28 HGT events or genes), transporters (24 HGT events or genes) and toxin biosynthesis systems (28 HGT events transferring a total of 69 genes) have all been subjected to HGT into osmotrophic eukaryotic microorganisms, such as fungi and oomycetes (see Supplementary informa tion S1-S3 (tables) and REFS 87,88). This group of 121 HGT candidates predicted to function in osmotrophic and public goods phenotypes represents more than 32% of the 370 collated HGTs into fungi 76,87,88 and oomycetes 89,96 . We therefore propose that HGT has played a part in the generation, protection and acquisition of public goods by osmotrophic eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we collated all published examples of fungal 76,87 and oomycete 89,96 genes that were acquired by HGT and encode secreted depolymerizing enzymes (Supplementary information S1 (table)) and transporter proteins (Supplementary information S2 (table)). These lists are derived from a larger collated list of previously published and revalidated HGT studies in fungi (a total of 323 genes 76,87 ), recent studies focusing on HGT of fructose transporter genes 88 and ammonium transporter genes 87 into fungi (ten and two transfers, respectively), and individual studies of HGT into oomycetes (a further 35 genes 89,96 ), giving 370 genes in total.…”
Section: Spiteful Behaviourmentioning
confidence: 99%
“…This topology supports an analysis by Gotesson et al (2002) showing that GH28s from the Stramenopile Phytophthora cinnamomi are more closely related to fungal GH28s than with those from plants. Furthermore, Phytophthora species have acquired multiple gene families laterally from distantly related plantdegrading fungi (Andersson, 2006;Soanes et al, 2007;Belbahri et al, 2007;Richards and Talbot, 2007), and similar processes likely resulted in the observed distribution of the pectinase gene family. Mucoromycotina is a basal group of fungi "incertae sedis" (Hibbett et al, 2007), and GH28s from this group form a well-supported clade of unannotated GH28 homologs (Supplementary File 2).…”
Section: Distribution Of Gh28 Clades Among Phylamentioning
confidence: 99%